Growth and quality of hydroponic cultivated spinach (Spinacia oleracea L.) affected by the light intensity of red and blue LEDs - Nguyen, Thi-Phuong-Dung; Vu, Ngoc-Thang; Nguyen, Quang-Thach; Tran, Thi-Thanh-Huyen; Cao, Phi-Bang; Kim, Il-Seop; Jang, Dong-Cheol (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aimed to evaluate the effect of four light intensities (90, 140, 190 and 240 μmol m-2 s-1) provided by red-blue LED light (spectrum ratio: R660/B450 = 4/1) on the growth and quality of hydroponic cultivated spinach. The results showed that when the light intensity increased, plant height, leaf number, root length, leaf width, shoot fresh weight, shoot dry weight, root fresh weight and root dry weight were increased but specific leaf weight and shoot-to-root ratio did not increase. The highest values of growth parameters were observed under 190 μmol m-2 s-1 treatment, while the lowest values were observed under 90 μmol m-2 s-1 treatment. At higher light intensities, K+, oxalic acid and nitrate contents tended to decrease but not Ca2+ content. Meanwhile, the highest values of Fe2+, crude fiber, soluble-solids, total polyphenol and vitamin C contents were observed under 190 μmol m-2 s-1 treatment, but 190 μmol m-2 s-1 treatment showed the lowest organic acid content. Our results indicated that among all experimental lighting treatments, 190 μmol m-2 s-1 light intensity showed the best effect on the growth and quality of hydroponic cultivated spinach.